Open lung biopsy performed in idiopathic pulmonary fibrosis is a safe procedure - Marjański, Tomasz; Halman, Joanna; Taniewska, Sonia; Burzyńska, Natalia; Piekarska, Anna; Sawicka, Wioletta (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease with a fatal prognosis. The diagnosis is made on the basis of high-resolution computed tomography and histological examination in selected cases. Aim : To determine the risk of complications of open lung biopsy performed in patients with IPF. Material and methods : We performed a retrospective analysis of 51 patients who underwent diagnostic excision of pulmonary parenchyma due to IPF in the period 1995–2014. We assessed the complication rate, length of drainage, postoperative period and 30-day mortality. We compared the results of treatment in the groups of patients operated on with thoracotomy and videothoracoscopy. Results : The mean age of patients was 58 (47% female, 53% male) forced vital capacity (FVC) was 81%, forced expiratory volume in 1 s (FEV 1 ) was 80% and body mass index (BMI) was 27 kg/m 2 . Thoracotomies (lateral, muscle sparing or anterior) were performed in 20 patients between 1995 and 2012 and videothoracoscopy in 31 patients operated on in the years 2009–2014. Patients in study groups did not differ considering age (p = 0.40), gender (p = 0.81), FVC (p = 0.08), FEV 1 (p = 0.13) or BMI (p = 0.75). Postoperative complications occurred in 3.9% of patients (atrial arrhythmia 1.9% and recurrent pneumothorax 1.9%) with equal incidence in both study groups (p = 0.75). Median stay after thoracotomy was 4 days while after videothoracoscopy it was 3 days (p = 0.04). Conclusions : Open lung biopsy performed on patients with IPF is a safe procedure. Open lung biopsy performed through thoracotomy could be as safe as through VATS, however is characterized by longer postoperative stay.